Establishing clinical governance model in primary health care: A systematic review - Leila Hosseini Ghavamabad; Abbas Vosoogh-Moghaddam; Rouhollah Zaboli; Mohsen Aarabi (Wolters Kluwer Medknow Publications, 2021)
Clinical governance is a systematic approach to enhancing the quality of primary health care and ensuring high clinical standards, responsiveness to performance, and continuous improvement in service quality. The objective of the current study was to investigate the global experiences of clinical governance in primary health care. In the present systematic review, relevant articles from different countries were searched in various databases such as MD PubMed from Medline portal, Emerald Springer link, ProQuest, Cochrane, Scopus, Web of Science, and Consult until April 2019. The searched articles were checked through CASP and PRISMA checklists, and their results were extracted. Of the 17 selected studies, 16 belonged to developed countries, including England (13), Australia, Italy, and New Zealand, and one was from Turkey. The findings were divided into three general categories: (1) principles of effectiveness and risk management, (2) deployment requirements such as structural and organizational needs, resource and communication, and information management, and (3) barriers of clinical governance toward providing primary health care. it is recommended that a suitable framework or model be developed and designed adapted to the local culture and taking into account all effective dimensions for a proper establishment and implementation of clinical governance in primary health care.